Effect of Financial Risk on the Earnings Response of Bank in Indonesisa, the Philippines, South Korea and Thailand - Soh, Wei Ni (2009)
The East Asian Financial crisis started at the beginning of July 1997. The crisis had a major impact on the banking industries in East Asian resulting in significant structural changes taking place in the banking sectors of the crisis-affected countries. This paper expands on the ideas of an earlier paper titled “Abnormal Returns of Bank stocks and their Factor-Analyzed Determinants” written by Cheng and Ariff (2007). This paper also attempts to analyze the Earnings Response Coefficients (ERC) for four (4) selected East Asian countries’ commercial banks and the effect of financial risks on the earnings response after the crisis and bank restructuring. This study uses the earnings response methodology and applies Sharpe’s Market Model, naive expectation model and factored principal components analyses. The countries selected are Thailand, Korea, Indonesia and Philippine and data resources are mainly accessed from the monthly closing prices in Bankscope financial data, Company Annual Reports, and the annual earnings announcements obtained from various Stock Exchange Central web-sites from 2000 to 2008. The findings show that Korea and Indonesian’s credit risk factors are significantly affecting their ERC and this is consistent with the results obtained for Malaysia by Cheng and Ariff (2007). Whereas additional interest risk factor and solvency factor are also significantly affecting Thailand’s ERC, surprisingly results from the Philippine’s show that their risk factors are not significantly affected because they are closely linked with the US and they are least affected by the financial crises. The findings provide new evidences on the effect of financial risk on ERC in banks’ stocks of East Asian countries with unique historical backgrounds and financial authorities’ policy decisions.